La producción de cacao en Matina y la rebelión de los indígenas Urinamas (Costa Rica 1650-1690) - Solórzano Fonseca, Juan Carlos (2012)
This article analyzes the beginnings of cacao production in the Central Caribbean region of Costa Rica, starting in 1650. The intention of the Spaniards was to force the Indians to work in the Matina cacao plantations.  To control the Indian labor force, the Franciscan friars went to the Indian territories and tried to transfer the Urinama Indians to new founded reduction villages. There, the Indians were to receive Christian indoctrination and sent to work for the cacao groves owners.  But the Indians revolted and fled to the neighboring high mountains. Finally the cacao plantations were worked by African slaves acquired from merchants from Holland and England.